IDENTIFIKASI LAJU EROSI DAN LAJU SEDIMENTASI PADA WADUK WONOSARI KABUPATEN BENGKALIS - Saily, Randhi; Jusi, Ulfa (Jurnal Tekno, 2021)
Generally, people who live in island areas depend on the management of water resources, such as the distribution of raw water from reservoirs. Bengkalis Regency is an island area and has a Wonosari reservoir which functions as a source of raw water for the people. Often, there is drought or lack of water supply to the people during the summer. One of the factors indicating the cause is the reduced volume of water storage in the reservoir due to sedimentation which can be calculated using the equations of erosion rate and sedimentation rate. The method used is the explorative-survey which obtains supporting data from direct field surveys and spatial, environmental and territorial approaches. The results for this study proved that sedimentation in the reservoir did not significantly affect the occurrence of water shortages which caused water needs to be not fulfilled in the community. The rates of erosion and sedimentation rates are 5.415 ton/ha/yr and 0.164 ton/ha/yr (very light erosion hazard category).